Computational evaluation of quinones of Nigella sativa L. as potential inhibitor of dengue virus NS5 - Roney, Miah; Dubey, Amit; Muhammad Hassan, Nasir; Huq, A. K. M. Moyeenul; Tufail, Aisha; Saiful Nizam, Tajuddin; Normaiza, Zamri; Mohd Fadhlizil Fasihi, Mohd Aluwi (Taylor & Francis, 2023)
Aedes aegypti is the primary vector for the transmission of the dengue virus, which causes dengue fever, dengue hemorrhagic illness and dengue shock syndrome. There is now no antiviral medication available to treat DENV, which kills thousands of people each year and infects millions of individuals. A possible target for the creation of fresh and efficient dengue treatments is the DENV-3 NS5 MTase. So, Nigella sativa quinones were examined using in silico methods to find natural anti-DENV compounds. The in silico docking was conducted utilising the Discovery Studio software on the quinones of N. sativa and the active site of the target protein DENV-3 NS5 MTase. In addition, the druggability and pharmacokinetics of the lead compound were assessed. Dithymoquinone was comparable to the reference compound in terms of its ability to bind to the active site of target protein. Dithymoquinone met the requirements for drug likeness and Lipinski’s principles, as demonstrated by the ADMET analysis and drug likeness results. The current study indicated that the dithymoquinone from N. sativa had anti-DENV activity, suggesting further drug development and dengue treatment optimisation